Educational administration concepts and practices - Lunenburg, Frederick C.; Ornstein, Allan C. (Wadsworth, Cengage ‪Learning, 2012)
Discusses topics necessary for an understanding of educational administration, balancing theory and research with practical coverage of culture, change, curriculum, human resources administration, diversity, effective teaching strategies, and supervision of instruction.